抗コラプシン反応媒介タンパク質2抗体の腎臓癌細胞遊走抑制作用 - 山本, 泰弘; 矢上, 達郎; 高馬, 宏美 (日本薬理学会年会要旨集, 2021)
Renal cell carcinoma (RCC) accounts for 2-3% of all malignancies. After surgical resection, approximately 40% of patients develop metastases. The 5-year survival probability for patients with metastatic renal cell carcinoma is less than 10% due to resistance to chemotherapy and radiation therapy. Therefore, there is an urgent need to establish novel therapies for the treatment of metastatic RCC. It has been reported that collapsin response mediator protein (CRMP), a cytoplasmic protein involved in the formation of neuronal axons, also contributes to the progression of malignant tumors. In the present study, we evaluated the effects of anti-CRMP2 antibody on the migration of Caki-2 RCC cells. The treatment with anti-CRMP2 antibody decreased the migration of Caki-2 cells. Our present study proposes the therapeutic potential of CRMP inhibition for prevention of RCC metastasis.